Sudan the failure and division of an African state - Cockett, Richard (Yale University Press, 2016)
In this fascinating and immensely readable book, the Africa editor of the Economist gives an absorbing account of Sudan's descent into failure and what some have called genocide. Drawing on interviews with many of the main players, Richard Cockett explains how and why Sudan has disintegrated, looking in particular at the country's complex relationship with the wider world.